Processes of care and outcomes for homeless patients hospitalised for cardiovascular conditions at safety-net versus non-safety-net hospitals: cross-sectional study - Atsushi Miyawaki; Yusuke Tsugawa; Dhruv Khullar (BMJ Open)
Objectives Evidence suggests that homeless patients experience worse quality of care and poorer health outcomes across a range of medical conditions. It remains unclear, however, whether differences in care delivery at safety-net versus non-safety-net hospitals explain these disparities. We aimed to investigate whether homeless versus non-homeless adults hospitalised for cardiovascular conditions (acute myocardial infarction (AMI) and stroke) experience differences in care delivery and health outcomes at safety-net versus non-safety-net hospitals.Design Cross-sectional study.Setting Data including all hospital admissions in four states (Florida, Massachusetts, Maryland, and New York) in 2014.Participants We analysed 167 105 adults aged 18 years or older hospitalised for cardiovascular conditions (age mean=64.5 years; 75 361 (45.1%) women; 2123 (1.3%) homeless hospitalisations) discharged from 348 hospitals.Outcome measures Risk-adjusted diagnostic and therapeutic procedure and in-hospital mortality, after adjusting for patient characteristics and state and quarter fixed effects.Results At safety-net hospitals, homeless adults hospitalised for AMI were less likely to receive coronary angiogram (adjusted OR (aOR), 0.42; 95% CI, 0.36 to 0.50; p<0.001), percutaneous coronary intervention (aOR, 0.52; 95% CI, 0.44 to 0.62; p<0.001) and coronary artery bypass graft (aOR, 0.43; 95% CI, 0.26 to 0.71; p<0.01) compared with non-homeless adults. Homeless patients treated for strokes at safety-net hospitals were less likely to receive cerebral arteriography (aOR, 0.23; 95% CI, 0.16 to 0.34; p<0.001), but were as likely to receive thrombolysis therapy. At non-safety-net hospitals, we found no evidence that the probability of receiving these procedures differed between homeless and non-homeless adults hospitalised for AMI or stroke. Finally, there were no differences in in-hospital mortality rates for homeless versus non-homeless patients at either safety-net or non-safety-net hospitals.Conclusion Disparities in receipt of diagnostic and therapeutic procedures for homeless patients with cardiovascular conditions were observed only at safety-net hospitals. However, we found no evidence that these differences influenced in-hospital mortality markedly.